Pengetahuan Ibu tentang Imunisasi terhadap Kesehatan Balita di Desa Sumput Kecamatan Driyorejo Kabupaten Gresik - Retno Oktavianingsih; Wara Pramesti (J STATISTIKA: Jurnal Imiah Teori dan Aplikasi Statistika, 2017)
Immunization As one of the preventive efforts to prevent the disease through immunity should be carried out continuously, thoroughly, and implemented according to standards as provide health protection and break the chain of transmission. With 62 respondents mothers to know maternal education, mother's job, mother's age and mother's knowledge about immunization. Based on test analysis of Hormer and Lemeshow binary logistic regression equation can be used to analyze mother's knowledge about health immunization (Y). This is known because the sig value> 0.05. From the result of regression anaisis above is not generated by regression equation, interpretation from analysis seen in discussion chapter of model interpretation. Based on the Wald test results known independent variables do not significantly affect the dependent variable. Based on Nagelkerke determination coefficient of 0,148 or 14,8%. This means that mother's knowledge about immunization does not affect toddler health in general. There is no relationship between maternal education, mother's job, mother's age, and mother's knowledge about immunization against the health variable toddler because of the height of any mother's education, mother's job, mother's age, and mother's knowledge but if the toddler is not paid attention seriously will affect health Toddler.